Tanggung Jawab Orang Tua Memberikan Pendidikan Moral Kepada Anak untuk Mewujudkan Bonum Prolis Sebagai Tujuan Perkawinan Katolik - Nosar, Ludovika Anjelin Agnes; Avan, Komela; Sidi, Fabianus (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
The research aims to understand parents' knowledge about the elements of moral education and the forms of moral education application to children concerning solidarity, justice, and honesty imparted by parents to realize bonum prolis as the goal of Catholic marriage. A descriptive qualitative approach is employed, utilizing interview, observation, and documentation methods. The research informants consist of nine parents with a marriage duration of 5–15 years. The study is conducted from December 2023 to March 2024. Data analysis involves technique triangulation and source triangulation. The results indicate that parents possess knowledge of the elements of moral education, such as mutual respect, helping one another, justice, and honesty. The application of moral education in solidarity includes avoiding harsh words, involving children in social activities, praying for friends, respecting those who worship, and teaching the words